Government Amnesty Programme and Peace Efforts in the Niger Delta Region: An Analysis of Newspapers’ Coverage - Adeyemi Aderogba (European Scientific Journal, ESJ, 2016)
Nigeria has undergone not a few crises since the country gained political independence from Great Britain in 1960. One of the current crises is the agitation of the youths of the oil-rich Niger Delta region for the control of oil and gas resources located in their region. In a bid to stem down the tide of violent activities and its attendant obstruction of the economic development of not only the region but also that of the nation at large, the government introduced what it termed "Presidential Amnesty Programme". This paper examined the newspapers' coverage of the situation in the Niger Delta region at a period considered the peak of the crisis, that is 2007 and 2009 as well as the coverage of the situation during the amnesty period (from 6th August to 4th October 2009). Content analysis was employed for this study. The study period was divided into two, that is, pre- amnesty period and amnesty period. Two popular national daily newspapers were examined, that is the Punch and the Guardian newspapers. A total number of three hundred and two copies of the two newspapers selected for the study were content analyzed. One hundred and eighty two were examined for the first period and one hundred and twenty copies were looked into for the second period. Social responsibility theory was considered relevant to the study. It was discovered that violent activities were well pronounced before the commencement of amnesty programme. 47.8 percent of the newspapers content on the region for the period was on violent activities such as vandalism of oil installations, violent attacks on oil workers and kidnappings. However, "Presidential Amnesty Programme" significantly reduced tension as well as crime in the region. Only 13 percent of all the stories published in the two newspapers during the amnesty programme were on violence. Huge numbers of the former militants (about 30,000) embraced reconciliation and rehabilitation. Amnesty programme so far has proved to be huge success.